Problematyka relacji osobowych w ujęciu Janusza Korczaka w odniesieniu do wychowawców i nauczycieli. Rekonstrukcja teoretyczno-empiryczna - Jolanta Kruk; Mariola Pałka-Pilecka (Problemy Wczesnej Edukacji)
Janusz Korczak’s works and pedagogical activities can be perceived on different levels. This text is a proposal of the analysis of Korczak’s achievements in the context of building personal relation-ships in the process of educating with respect to alumni and teachers-educators. In Conclusions the created reconstruction of the way Janusz Korczak understood mutual relations was interpreted in the context of the idea of dialogical personalism. It is a theoretical and empirical article based on Korczak’s works, the materials collected during a visit to Korczakianum. The method applied in this reconstruction was the fusion of the analysis of selected works and the open interview with the managers of this research lab.